Investigation and outcomes in patients with nonspecific pleuritis: results from the International Collaborative Effusion database - Anand Sundaralingam; Avinash Aujayeb; Karl A. Jackson; Emilia I. Pellas; Irfan I. Khan; Muhammad T. Chohan; Roos Joosten; Anton Boersma; Jordy Kerkhoff; Silvia Bielsa; Jose M. Porcel; Ales Rozman; et al. (ERJ Open Research, 2023)
Introduction We present findings from the International Collaborative Effusion database, a European Respiratory Society clinical research collaboration. Nonspecific pleuritis (NSP) is a broad term that describes chronic pleural inflammation. Various aetiologies lead to NSP, which poses a diagnostic challenge for clinicians. A significant proportion of patients with this finding eventually develop a malignant diagnosis. Methods 12 sites across nine countries contributed anonymised data on 187 patients. 175 records were suitable for analysis. Results The commonest aetiology for NSP was recorded as idiopathic (80 out of 175, 44%). This was followed by pleural infection (15%), benign asbestos disease (12%), malignancy (6%) and cardiac failure (6%). The malignant diagnoses were predominantly mesothelioma (six out of 175, 3.4%) and lung adenocarcinoma (four out of 175, 2.3%). The median time to malignant diagnosis was 12.2 months (range 0.8–32 months). There was a signal towards greater asbestos exposure in the malignant NSP group compared to the benign group (0.63 versus 0.27, p=0.07). Neither recurrence of effusion requiring further therapeutic intervention nor initial biopsy approach were associated with a false-negative biopsy. A computed tomography finding of a mass lesion was the only imaging feature to demonstrate a significant association (0.18 versus 0.01, p=0.02), although sonographic pleural thickening also suggested an association (0.27 versus 0.09, p=0.09). Discussion This is the first multicentre study of NSP and its associated outcomes. While some of our findings are reflected by the established body of literature, other findings have highlighted important areas for future research, not previously studied in NSP.